Vector mechanics for engineers - Dynamics : - Beer, Ferdinand Pierre (WCB McGraw-Hill, 1997)
The sixth edition of the introductory text to the dynamics of vector mechanics. The new edition contains 36 new critical thinking exercises, new art work and free Windows interactive software which visually develops concepts of dynamics using animations.